PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2021 - Hastini, Frizka Dwi; Maryono, Maryono; Badjuri, Achmad (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The objective of this inquiry is to scrutinize the extent to which board size, institutional ownership, audit committees, and corporate magnitude influence the fiscal performance of manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. This examination incorporates a sample of 248 firms selected through a purposive sampling technique. The study employs multiple linear regression analysis to evaluate the data. The findings of this assessment indicate that institutional ownership and corporate magnitude exert a significantly positive effect on financial performance, whereas board size and audit committee presence bear no substantial influence on financial outcomes